Efficacy and safety of losartan in childhood immunoglobulin A nephropathy: a prospective multicenter study - Hyesun Hyun; Yo Han Ahn; Eujin Park; Hyun Jin Choi; Kyoung Hee Han; Jung Won Lee; Su Young Kim; Eun Mi Yang; Jin Soon Suh; Jae Il Shin; Min Hyun Cho; Ja Wook Koo; et al. (Korean Society of Pediatric Nephrology, 2023)
Purpose Angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers (ARBs) are frequently employed to counteract the detrimental effects of proteinuria on glomerular diseases. However, the effects of ARBs remain poorly examined in pediatric patients with immunoglobulin A (IgA) nephropathy. Herein, we evaluated the efficacy and safety of losartan, an ARB, in pediatric IgA nephropathy with proteinuria. Methods This prospective, single-arm, multicenter study included children with IgA nephropathy exhibiting proteinuria. Changes in proteinuria, blood pressure, and kidney function were prospectively evaluated before and 4 and 24 weeks after losartan administration. The primary endpoint was the difference in proteinuria between baseline and 24 weeks. Results In total, 29 patients were enrolled and received losartan treatment. The full analysis set included 28 patients who received losartan at least once and had pre- and post-urinary protein to creatinine ratio measurements (n=28). The per-protocol analysis group included 22 patients who completed all scheduled visits without any serious violations during the study period. In both groups, the mean log (urine protein to creatinine ratio) value decreased significantly at 6 months. After 24 weeks, the urinary protein to creatinine ratio decreased by more than 50% in approximately 40% of the patients. The glomerular filtration rate was not significantly altered during the observation period. Conclusions Losartan decreased proteinuria without decreasing kidney function in patients with IgA nephropathy over 24 weeks. Losartan could be safely employed to reduce proteinuria in this patient population. ClinicalTrials.gov trial registration (NCT0223277)